2016
DOI: 10.3892/ijo.2016.3491
|View full text |Cite
|
Sign up to set email alerts
|

Invasion and increased expression of S100A4 and CYR61 in mesenchymal transformed breast cancer cells is downregulated by GnRH

Abstract: S100 calcium binding protein A4 (S100A4) and cysteine-rich angiogenic inducer 61 (CYR61) play important roles in epithelial-mesenchymal-transition (EMT), invasion and metastasis by promoting cancer cell motility. Recently we were able to show that invasion of GnRH receptor-positive breast cancer cells is time- and dose-dependently reduced by GnRH analogs. We have now analyzed whether GnRH treatment affects S100A4 and CYR61 in mesenchymal transformed breast cancer cells. S100A4 and CYR61 expression was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 47 publications
1
30
0
2
Order By: Relevance
“…About 50–64% of human breast cancers have high-affinity GnRH receptors, according to various studies ( 16 19 ). A more recent study reported that GnRH receptor expression was detected in 67% of hyperplasia cases (4 out of 6), in 100%of benign fibroadenoma cases (3 out of 3), in 100% of carcinoma in situ cases (4 out of 4), and in 71% cases of malignant breast cancers (22 out of 31) ( 20 ). The therapeutic options today are incredibly limited in particular for triple-negative breast cancers (TNBCs), which do not exhibit either the estrogen receptor α (ERα) or the progesterone receptor and do not overexpress the HER2-neu gene.…”
Section: Expression Of Gonadotropin-releasing Hormone (Gnrh) and Its mentioning
confidence: 99%
See 3 more Smart Citations
“…About 50–64% of human breast cancers have high-affinity GnRH receptors, according to various studies ( 16 19 ). A more recent study reported that GnRH receptor expression was detected in 67% of hyperplasia cases (4 out of 6), in 100%of benign fibroadenoma cases (3 out of 3), in 100% of carcinoma in situ cases (4 out of 4), and in 71% cases of malignant breast cancers (22 out of 31) ( 20 ). The therapeutic options today are incredibly limited in particular for triple-negative breast cancers (TNBCs), which do not exhibit either the estrogen receptor α (ERα) or the progesterone receptor and do not overexpress the HER2-neu gene.…”
Section: Expression Of Gonadotropin-releasing Hormone (Gnrh) and Its mentioning
confidence: 99%
“…The S100 calcium-binding protein A4 (S100A4) and the cysteine-rich angiogenic inducer 61 (CYR61, CCN1) promote cancer cell motility and thus play important roles in EMT, invasion, and metastasis ( 64 68 ). Highly invasive MDA-MB-231 breast cancer cells exhibit high expression of both genes ( 20 ). An increased CYR61 level correlates with a poor prognosis, poor lymph node status, and metastatic propagation ( 69 , 70 ).…”
Section: Antimetastatic Action Of Gnrh In Human Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…Both endogenous and extracellular S100A4 have been linked to metastasis. Endogenous S100A4 is known to enhanced cell motility and invasion (Grundker et al ., 2016), while extracellular, stromal S100A4 has been shown to instigate inflammatory events promoting metastasis (Hansen et al ., 2014). …”
Section: Introductionmentioning
confidence: 99%